ANALISIS KUALITAS LAYANAN TERHADAP KEPUASAN MAHASISWA: STUDI KASUS PADA STIE MDP PALEMBANG - Ruth Samantha Hamzah; Diaz Almalik (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2019)
This study aims to analyze the relationship of service quality towards student satisfaction at STIE MDP Palembang in 2016. This is a quantitative study which collected data from questionnaires that were distributed to 30 samples by purposive sampling method. Gap analysis and quadrant analysis have been used in this study. The results have shown that the level of gap service between expectation and perception of customers toward service quality of STIE MDP were measured by the calculation of each dimensions. This measurement can be seen on gap 2, 3, and 4 which showed the dominant positive gap scores, respectively. Therefore, periodic improvements are needed in order to enhance the service quality in achieving student satisfaction optimally.